Closing the Gap : Improving Laws Protecting Women from Violence - Sakhonchik, Alena; Santagostino Recavarren, Isabel; Tavares, Paula (World Bank, Washington, DC, 2017)
Women, business and the law examines where economies provide legal protection for women and girls in areas such as child marriage, domestic violence, and marital rape. It also collects data on remedies, such as the existence and scope of protection orders for victims of domestic violence. Violence thwarts women’s economic empowerment by limiting their ability to exercise agency and make choices. Violence against women and girls both reflects and reinforces inequalities between women and men. Where a girl can be legally married before she turns 18, she has less opportunity to make choices about her future. Where a woman suffers abuse from her husband, her health and psychological well-being are threatened and her capacity to work and function socially are impaired. If she is not able to work, she is forced into a subordinate position, both psychologically and economically, and the cycle of violence persists. Legal protection is crucial to reduce impunity and open avenues for redress. Yet Women, Business and the Law finds persisting gaps in laws protecting women from violence. Countries are increasingly protecting girls and women from violence. For example, between 2013 and 2015, Kenya, Luxembourg, Nicaragua, and Uruguay all raised the age of marriage for girls. Tonga’s 2013 Family Protection Act explicitly criminalizes marital rape. Georgia has amended its criminal code to expand the grounds of liability for domestic crimes, including rape, to spouses and other family members. Moreover, it reformed the Law on the Elimination of Domestic Violence to provide for removal of the perpetrator from the home. In its new penal code, Mozambique has amended Article 400, which had been in place since 1886 and allowed charges to be dropped if a rapist married his victim. And Belarus, Lebanon, Papua New Guinea, and Tonga adopted new laws on domestic violence that provide for protection orders. While there has clearly been progress, major gaps still need to be addressed. That Malawi and 8 other economies have raised the marital age shows movement in a positive direction. The adoption in the past 2 years of new domestic violence laws in some economies and more comprehensive provisions in others worldwide is also a telling indication of progress. But more is needed. Among the priorities of the new Sustainable Development Goals (SDGs) are ‘eliminating all forms of violence against women and girls in the public and private spheres’ and ‘eliminating all harmful practices, such as child, early and forced marriage,’ which recognize the need for enhanced legal protection for girls and women worldwide. International and regional commitments and instruments pave the way for change. And while the existence of more and better laws is a critical first step, better enforcement of the law is necessary to ensure protection for women. Only when women and girls are fully protected from violence will they be able to enjoy the same autonomy, freedom, and opportunities as men.